Energy intensity and its determinants in China: an empirical study based on ARDL-VECM approach. Issue 3 (3rd July 2017) - Du, Dan; Lei, Hongyan
ABSTRACT: The present study aims to better understand the relationship between energy intensity and its determinants including energy price, technological progress, economic structure, and energy mix using the autoregressive distributed lag (ARDL) bounds approach and vector error correction model technique. Based on China's time series over 1985‒2014, the ARDL bounds approach yields empirical evidence that confirms the existence of long run relationship between energy price, technological progress, economic structure, energy mix, and energy intensity. The results show that technological progress is an important driver for the declining energy intensity in short and long run. Energy price has not been demonstrated as an important role in decreasing energy intensity in the short run. The high share of coal use in total energy use may be responsible for China's high energy intensity. However, the relative change in economic sectors plays a minor role in energy intensity reduction during the past years. In the long run, technological progress, energy mix and energy prices Granger cause energy intensity, but not vice versa except for the energy mix.